NHERF1 regulates actin cytoskeleton organization through modulation of α‐actinin‐4 stability. Issue 2 (2nd October 2015) - Sun, Licui; Zheng, Junfang; Wang, Qiqi; Song, Ran; Liu, Hua; Meng, Ran; Tao, Tao; Si, Yang; Jiang, Wenguo; He, Junqi
Abstract : The actin cytoskeleton is composed of a highly dynamic network of filamentous proteins, yet the molecular mechanism that regulates its organization and remodeling remains elusive. In this study, Na + /H + exchanger regulatory factor (NHERF)‐1 loss‐of‐function and gain‐of‐function experiments reveal that polymerized actin cytoskeleton (F‐actin) in HeLa cells is disorganized by NHERF1, whereas actin protein expression levels exhibit no detectable change. To elucidate the molecular mechanism underlying actin cytoskeleton disorganization by NHERF1, a combined 2‐dimensional electrophoresis‐matrix‐assisted laser desorption/ionization‐time of flight mass spectrometry approach was used to screen for proteins regulated by NHERF1 in HeLa cells. α‐Actinin‐4, an actin cross‐linking protein, was identified. Glutathione S ‐transferase pull‐down and coimmunoprecipitation studies showed the α‐actinin‐4 carboxyl‐terminal region specifically interacted with the NHERF1 postsynaptic density 95/disc‐large/zona occludens‐1 domain. The NHERF1/α‐actinin‐4 interaction increased α‐actinin‐4 ubiquitination and decreased its expression levels, resulting in actin cytoskeleton disassembly. Our study identified α‐actinin‐4 as a novel NHERF1 interaction partner and provided new insights into the regulatory mechanism of the actin cytoskeleton by NHERF1.—Sun, L., Zheng, J., Wang, Q., Song, R., Liu, H., Meng, R., Tao T., Si, Y., Jiang, W., He, J. NHERF1 regulates actin cytoskeleton organization through modulation of α‐actinin‐4 stability. FASEB J. 30, 578‐589 (2016). www.fasebj.org